Phenytoin and Folic Acid - J Gordon Millichap (Pediatric Neurology Briefs, 1992)
The pharmacokinetics of phenytoin (PHT) before and after administration of 1 and 5 mg of folic acid is reported from the Colleges of Pharmacy and Medicine, University of Iowa, Iowa City and University of Health Sciences/The Chicago Medical School, Chicago, IL.